take out the x
x(a-b)=6
x=6/(a-b)
2006-11-22 06:32:50
·
answer #1
·
answered by 7
·
3⤊
0⤋
ax - bx = 6
Use the distributive property to isolate x:
(a - b)x = 6
Now divid bothe sides by (a - b):
x = 6 / (a - b)
2006-11-22 06:33:41
·
answer #2
·
answered by Anonymous
·
2⤊
1⤋
Factor x out
ax-bx=6
x(a-b)=6
x=6/(a-b)
Note a cannot equal b as division by 0 occurs which is not allowed
2006-11-22 06:33:09
·
answer #3
·
answered by Oz 4
·
2⤊
1⤋
ax - bx = 6
x(a-b)=6
>>>x=6/(a-b)
subject to the restriction
{a is not equal to b}
i hope that this helps
2006-11-22 07:49:13
·
answer #4
·
answered by Anonymous
·
1⤊
1⤋
(x)=x^3+ax^2+bx-6 if remainder when f(x) is divided by (x-2) = remainder when f(x) is divided by (x+2) show that b=-4
By the remainder theorem, f(2)=f(-2). Let's plug in the numbers and see
what happens:
8 + 4a + 2b - 6 = -8 + 4a -2b - 6
16 + 4b = 0
4b = -16
b = -4
good luck, hope this is right
2006-11-22 06:37:04
·
answer #5
·
answered by missey01_uk 3
·
1⤊
2⤋
ax - bx = 6
Factor out x to get:
x(a-b) = 6
Now divide both sides by a-b to get
x = 6/(a-b)
2006-11-22 06:34:57
·
answer #6
·
answered by ironduke8159 7
·
2⤊
1⤋
ax - bx = 6
Factor out an x
x(a-b) = 6
Divide both sides by (a-b)
x = 6/(a-b)
Note that a-b cannot be zero (because you can't divide by zero).
2006-11-22 06:32:57
·
answer #7
·
answered by MsMath 7
·
1⤊
2⤋
Take out a factor of x
x(a-b) = 6
Then divide both sides by (a-b)
x=6/(a-b)
note that this is not true when a=b because you can't divide by 0!
2006-11-22 06:42:15
·
answer #8
·
answered by drummanmatthew 2
·
1⤊
1⤋
x=6/(a-b)
2006-11-22 09:05:04
·
answer #9
·
answered by Just me 5
·
1⤊
1⤋
ax-bx=6
x(a-b)=6
x=6/(a-b)
2006-11-22 16:55:00
·
answer #10
·
answered by sam 3
·
0⤊
0⤋
ax - bx = 6
x(a - b) =6
So x = 6/(a - b)
2006-11-22 06:38:28
·
answer #11
·
answered by Wal C 6
·
2⤊
1⤋